2014
DOI: 10.1016/j.giq.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

When virtual reality meets realpolitik: Social media shaping the Arab government–citizen relationship

Abstract: a b s t r a c tSince most activists participating in the recent uprisings in Arab countries have been using social media to an unprecedented extent, public analyst and researchers have rushed to reflect on and explain the phenomena, often attributing a 'change agency' to social media as such. This argumentative research collects evidence from literature, recent surveys and focus groups in order to contextualize our understanding of the role of social media and its usage in reshaping the Arab government-citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Regarding the effects of VR on social media, there is a common understanding of its potential to transform the social interactions occurring on these online platforms, with a clear reconfiguration of traditional concepts and conversion among virtual and physical contexts (e.g. Klischewski, 2014;Lyntras et al, 2015). However, no shared vision seems…”
Section: T7 Communication and Social Media Studies On This Topic Are mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effects of VR on social media, there is a common understanding of its potential to transform the social interactions occurring on these online platforms, with a clear reconfiguration of traditional concepts and conversion among virtual and physical contexts (e.g. Klischewski, 2014;Lyntras et al, 2015). However, no shared vision seems…”
Section: T7 Communication and Social Media Studies On This Topic Are mentioning
confidence: 99%
“…With this tool it will be easier to go further in understanding antecedents of the outcomes of VR experiences. (Klischewski, 2014) Note. The example papers presented in the table are sorted by size of the correlation with the topic Table 1.…”
Section: Future Researchmentioning
confidence: 99%
“…Research indicated that Arab governments have deficiencies in their democracy and sometimes they lack such phenomenon at all. However, Islam as a religion adapted democracy through "Shura" (consultation) and ignored the autocratic style of governance [15] and Shura in the first Islamic era is compatible to the democracy in modern political life.…”
Section: A Deficiencies Of Traditional Government Communicationmentioning
confidence: 99%
“…Furthermore, at a time when politics is in sharp crisis, the need to re-ensure citizens' trust on politicians is immediate, leading the latter to use social media in order to communicate with their voters aiming at promoting e-dialogue. In the context of movements' organization, the Arab Spring or the movement in Taksim square seem to have relied on social networks enabling an extended organization of citizens [3,4] attempting for a mutual goal. Last but not least an increasing adoption of social media by government agencies should be noted in recent years, leading to e-governance.…”
Section: Introductionmentioning
confidence: 99%